The similarities and differences of HRM in higher education institutions in Hungary and England - Bodor, Mónika (Acta Scientiarum Socialium, 2011)
In this article I am examining the advancement of Human Resource Management in the Hungarian higher education institutions. After the period of implementation, in the last 10 years it showed a steady development, but its effectiveness, efficiency and the recognition of HRM among the academic staff lags behind the well-established and operating system in Western countries. Therefore, I analyzed HRM in English higher education institutions across England and compared it with its Hungarian counterpart. I intend to highlight similarities and differences of HR policy and practice used in higher education institutions in these two countries. Furthermore, I assessed the alignment of HR strategy within the overall institutional strategy and its effective support and contribution to the performance and development of the organization. The aim of this article is to recognize and identify „the elements of best practice” that could be found in effective HRM in English higher education institutions and making suggestions to significantly enhance the effectiveness of HRM in Hungarian higher education institutions.